A comparative study on the rheological properties of two coal water slurries with sodium tripolyphosphate as dispersant. Issue 3 (4th March 2022) - Rao, M. Ananda; Yerriswamy, Veerapuram; Pavan Kumar, M. V.; Narasaiah, N.
ABSTRACT: Coal water suspensions of two different Indian coals (namely Coal 1 and Coal 2 ) were successfully prepared and their rheological behaviors were tested in the shear rate range of 60–160 s −1 for the comparison. Sodium tripolyphosphate was employed as dispersant after testing its suitability for the coal samples in zeta potential and turbidity measurements. The percentage of solids loading and dispersant dosage were varied to study their effect on the rheological behavior. The rheological nature of the suspensions for different solids loading and dispersant dosages were predicted after fitting the obtained rheological data using the power law model. Shear thickening behavior was observed for the lower solids loading (10%, 20%) with no significant change in the viscosity–shear rate relations with the dispersant addition. Conversely, the effect of dispersant was quite significant and desirable at the higher solids loading (30%, 40%, 50%) with the observed shear thinning behavior. The transition from shear thickening to shear thinning was seen between 20% and 30% solids loading with the addition of dispersant. Coal 1 exhibited favorable pumpable characteristics with low apparent viscosity. The lower percentage of ash-bearing minerals and the chemical composition of Coal 1 were seen as the main reason for its superior flow characteristics in comparison with that of Coal 2 .